2006
DOI: 10.1074/jbc.m601704200
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock within the Cardiomyocyte Is Essential for Responsiveness of the Heart to Fatty Acids

Abstract: Cells/organs must respond both rapidly and appropriately to increased fatty acid availability; failure to do so is associated with the development of skeletal muscle and hepatic insulin resistance, pancreatic ␤-cell dysfunction, and myocardial contractile dysfunction. Here we tested the hypothesis that the intrinsic circadian clock within the cardiomyocytes of the heart allows rapid and appropriate adaptation of this organ to fatty acids by investigating the following: 1) whether circadian rhythms in fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 49 publications
5
142
0
1
Order By: Relevance
“…As such, both intracellular and extracellular factors should be considered as important mediators of circadian rhythms in cardiovascular function. We speculate that impairment of this molecular mechanism may contribute toward myocardial contractile dysfunction associated with pressure overload, diabetes mellitus, myocardial infarction, and/or shift work (conditions in which the circadian clock within the heart is known to be altered) (9,18,43,45,46). Future studies should focus on addressing this important hypothesis.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…As such, both intracellular and extracellular factors should be considered as important mediators of circadian rhythms in cardiovascular function. We speculate that impairment of this molecular mechanism may contribute toward myocardial contractile dysfunction associated with pressure overload, diabetes mellitus, myocardial infarction, and/or shift work (conditions in which the circadian clock within the heart is known to be altered) (9,18,43,45,46). Future studies should focus on addressing this important hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…In our CCM mice, the circadian clock within the heart is severely attenuated in a sex-independent manner, as demonstrated by attenuation of clock component and output gene circadian oscillations, without affecting circadian clocks within extracardiac tissues (9). Using this model, our laboratory has recently shown that the circadian clock within the cardiomyocyte is essential for responsiveness of the heart to fatty acids (9).…”
mentioning
confidence: 88%
See 3 more Smart Citations